Impact of Borrowers’ Specific Factors on Level of Non-Performing Loans of Nepalese Commercial Banks: A Perception of Bankers - Pant, Dinesh Kumar (Journal of Entrepreneurship & Management Studies, 2024)
The operations of banks are significantly shaped by non-performing loans (NPLs), which have an impact on risk management, financial stability, and the profitability and efficiency of commercial banks. The primary goal of the research is to examine how certain borrower characteristics affect the amount of non-performing loans that Nepalese commercial banks have. The study was conducted using a descriptive and causal-comparative research approach. The bank employees employed by the many commercial banks operating in the province of Karnali as well as their branch offices at the provincial level comprised the study’s population. A convenience sample strategy was used to gather the responses. 406 individuals provided the data, which was gathered through the structured questionnaire. Using SPSS software, descriptive and regression analysis were used to evaluate and interpret the survey results. The research findings indicate that the level of non-performing loans in Nepalese commercial banks is significantly influenced by certain criteria related to the borrowers